ENSINO JURÍDICO NA BAHIA: A (DES)VALORIZAÇÃO DA DOCÊNCIA COMO CARREIRA PROFISSIONAL (Revista Direito em Debate, 2019)
The lack of law degree courses in the country suggests the need for the creation and implementation of didactic-pedagogical training tools for undergraduate law graduates. This possibility is provided by the National Curriculum Guidelines, which allow the presence of aspects that make the course curriculum flexible and deserves to be explored, given that these professionals will be responsible for the formation of future generations of lawyers. The present work sought to investigate the existence of stimulus within the fourteen undergraduate law courses administered by the public universities of the state of Bahia in relation to the teaching career, as a professional career. Therefore, a literature review was conducted on the theme, and the Pedagogical Projects of these courses were analyzed, as well as the edicts of competitions for admission to higher teaching in its faculty. Research has shown that the vast majority of the analyzed courses do not have curriculum components or complementary activities that refer to teaching practice during graduation. The competition notices, however, value the professional who has the most didactics, through tiebreakers, as well as in the way of calculating the grade attributed to the didactic test. It is argued that the implementation of compulsory components of didactic-pedagogical preparation is vital to increase the quality of legal education in order to allow proper training for future generations of law students.
Keywords: Legal Education; Law; Teaching; Devaluation Teaching; Teacher Training; teaching professionalization